2017
DOI: 10.4236/jss.2017.59006
|View full text |Cite
|
Sign up to set email alerts
|

Shanghai Pilot Free Trade Zone and Its Effect on Economic Growth: A Counter-Factual Approach

Abstract: Together with the deepening of globalization and economic integration, trade and investment liberalization has played more important role in economic cooperation. Besides the free trade agreements among member countries, free trade zone is also considered to establish a favorable environment in order to attract foreign investment and promote economic growth of the areas laying inside and outside the zone. On the basis of economic reforming and trade liberalization initiative, China approved the establishment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…First, a macro perspective, scholars examining the policy effect of the establishment of PFTZ have used empirical analysis methods such as counterfactual analysis, synthetic control, and DID to evaluate the economic effect of PFTZ construction. They have revealed that institutional dividends released with the construction of PFTZ have effectively stimulated regional economic growth (Cai et al, 2021 ; Huang et al, 2017 ; Wang, 2013 ; Zheng et al, 2016 ; Zhang et al, 2018 ), facilitated the free flow of international capital (Yao and Whalley, 2015 ; Yao and Whalley, 2016 ; Chen et al, 2021 ), reinforced the spillover effect of regional knowledge (Li et al, 2020 ), promoted the development of e-commerce industry (Yang et al, 2021 ), maintained the sustainable development of regions (Liu et al, 2021a , b ), and elevated the efficiency of port operation (Liu et al, 2021a , b ; Fan et al, 2022 ). From a micro perspective and based on the previous analysis that focused on the regional port operation efficiency impact of PFTZ construction, Li et al ( 2021a , b ) further shed light on the effects of the construction of PFTZ on the performance of listed companies and conducted empirical researches using the DID method on it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, a macro perspective, scholars examining the policy effect of the establishment of PFTZ have used empirical analysis methods such as counterfactual analysis, synthetic control, and DID to evaluate the economic effect of PFTZ construction. They have revealed that institutional dividends released with the construction of PFTZ have effectively stimulated regional economic growth (Cai et al, 2021 ; Huang et al, 2017 ; Wang, 2013 ; Zheng et al, 2016 ; Zhang et al, 2018 ), facilitated the free flow of international capital (Yao and Whalley, 2015 ; Yao and Whalley, 2016 ; Chen et al, 2021 ), reinforced the spillover effect of regional knowledge (Li et al, 2020 ), promoted the development of e-commerce industry (Yang et al, 2021 ), maintained the sustainable development of regions (Liu et al, 2021a , b ), and elevated the efficiency of port operation (Liu et al, 2021a , b ; Fan et al, 2022 ). From a micro perspective and based on the previous analysis that focused on the regional port operation efficiency impact of PFTZ construction, Li et al ( 2021a , b ) further shed light on the effects of the construction of PFTZ on the performance of listed companies and conducted empirical researches using the DID method on it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, China has eased restrictions for foreign and Chinese individuals, allowing both groups to practice inbound and outbound investments in the capital market. Foreign investors can transfer funds between their Chinese domestic and overseas entities via twoway cash pooling without foreign exchange controls (Huang et. al., 2017).…”
Section: Financial Advantagesmentioning
confidence: 99%
“…As the main battleground for promoting high-quality development of China's trade activities in the new era, free trade zones have a profound impact on China's economic development. A series of innovative systems and policies implemented in free trade zones play an important role in accelerating capital financing, increasing knowledge spillovers, reducing trade costs, and promoting regional economic development [19], [20]. Tan et al (2015) [8] and Zhang et al (2018) [12]empirically tested the economic effects of establishing the Shanghai FTZ using the counterfactual method as well as the double difference method.…”
Section: Literature Reviewmentioning
confidence: 99%